Hungarian Monitoring, 30 June 1988 . [Magyar rádiófigyelő], 1988. június 30 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Moscow Party assembly - Press conference in Prague prior to Comecon session Domestic Affairs: - Grósz on Monday's mass demonstration - Parliament in session: the minister's letter on the Gabčíkovo-Nagymaros dam affair - Environmentalists' open letter to Parliament on the Gabčíkovo-Nagymaros dam affair - Romanian-Hungarian relations: László Paskai comments in “Új Ember” - EEC-Hungary agreement is born - Béla Bartók's ashes arrive in England Economy: - Minister for industry acknowledges unsuccessful development of industry Külpolitika: - Moszkvai pártértekezlet - Sajtóértekezlet Prágában a KGST ülésszak előtt Belpolitika: - Grósz a hétfői tömegdemonstrációról nyilatkozik - Parlamenti ülés: a miniszter levele a bős-nagymarosi vízlépcső ügyben - Környezetvédők levele Bős-Nagymaros ügyében az országgyűléshez - Román - Magyar viszony: Paskai László is nyilatkozik az Új Emberben - Megszületett a megállapodás az EGK és Magyarország között - Bartók Béla hamvai Angliába érkeztek Gazdaság: - Az ipari miniszter elismeri az elhibázott iparfejlesztést